(untitled) (Research, Society and Development, 2022)
Introduction: It is an established fact that empathic skills are essential for building the therapeutic bond, a basic element in the doctor-patient relationship. The loss of empathic ability with a subsequent negative impact on resilience has been reported by medical students during the clinical phases of the course. Among the various interventions proposed for the development and facilitation of the empathic relationship are the Balint groups. Objective: To evaluate the participation in Balint groups in the development of an empathic attitude in the relationship established with the patient. Methods: This is an analytical, observational, cross-sectional study, in which two groups were compared: “Balint Group” and “Control Group”, to which the Wagnild & Young Resilience Scale and the Interpersonal Reactivity Index were applied. Results: Of the 36 participants, 8 were members of the Balint Group and 28 were from academic leagues. The Resilience Scale showed statistical superiority in the group of academic leagues, with a mean score of 115.6 ±19.3 obtained by participants in the Balint Group and 129.4 ±14.6 by members of academic leagues. As for the collection of the Interpersonal Reactivity Index, the Balint Group was statistically superior, with a mean score of 79±8.6 in the Balint Group and 64.4±13.6 in the academic leagues. Conclusion: The results support a more optimistic view on the issue of empathy and resilience in the medical curriculum and encourage the initiative of training aimed at helping young medical students to take into account the emotional component of the doctor-patient relationship.